Small and Medium-Sized Businesses (SMB) in Oman: Data Protection in Digital Transformation Post-COVID-19 – Gap Analysis and Risk Mitigation - Singh, Sukhwinder (Digital Repository of Theses - SSBM Geneva, 2025)
The main purpose of this research emphasises on exploring the data-protection and security concerns with the implementation of digital transformation within SMBs in Oman. The research objective focuses on determining the impact of data-related issues on the implementation of digital transformation, determining significant data-related challenges faced by management as a result of technical progress and inadequate security, and identifying recommendations to address the cybersecurity threats. Three hypotheses were formulated through extensive literature review to achieve the research objective. Data were gathered by conducting surveys through close-ended questionnaires. The reliability of the questionnaires was performed using the pilot test by engaging 30 participants. Further, the survey involved 200 participants from the SMBs in Oman with at least 1 year of experience within SMBs who have adopted digital transformation within their business. The research has chosen a quantitative research methodology which has been analysed through statistical tests with the help of the SPSS software. To test hypothesis 1, Pearson correlation has been performed between the digital transformation and data-related issues indicating a positive and robust relationship between the two. To test hypothesis 2, one-sample t-test, and one-way ANOVA have been performed to determine the challenges related to data indicating the p-value to be less than 0.05. The findings suggested that the management has been impacted with the data-related challenges because of technical progress and inadequate security. Lastly, the 3rd hypothesis aimed at determining the recommendations that assists in reducing the cybersecurity threats by performing the regression analysis. The results indicated a robust and positive relationship between the dependent and independent variable, further determining the p-value to be less than 0.05. All the results from the study's hypothesis indicates a positive relationship between the adoption of digital transformation and data-related issues by determining the challenges along with the recommendations that help address the cybersecurity issues.